Simulating synergies between Climate Change Adaptation and Disaster Risk Reduction stakeholders to improve management of transboundary disasters in Europe. (October 2020) - Booth, Laura; Fleming, Kevin; Abad, Jaime; Schueller, Lynn A.; Leone, Mattia; Scolobig, Anna; Baills, Audrey
Abstract: Natural hazards and climate-related disasters disregard political borders, where additional barriers can complicate mitigation, response and recovery efforts within and between the sectors of Climate Change Adaptation (CCA) and Disaster Risk Reduction (DRR). The ESPREssO Project (Enhancing Synergies for Disaster Prevention in the European Union) aims to improve management of transboundary disasters by encouraging closer synergies between the CCA and DRR communities. Using targeted stakeholder interviews, questionnaires, Think Tank discussions and purpose-built serious games, ESPREssO draws on both CCA and DRR stakeholder experiences and informed perspectives in order to identify current gaps. Set within a fictitious border zone, ESPREssO's RAMSETE II serious game challenges CCA and DRR stakeholders in making coordinated decisions before, during and after a simulated disaster, in protection of population and critical infrastructure. Results highlight the essential role of local governance mechanisms as the sharp end of the policy wedge, with current examples of proactivity that require to be championed and supported at national level in order to thrive. These good practice examples reflect the fact that transboundary settings, despite their challenges, act as fertile ground for mutual growth, offering opportunities for CCA and DRR communities to find innovative ways to cooperate and unite in developing synergies and strengthening their mutual efforts towards resilience. Stakeholders emphasise a need to invest more resources in informal cooperation and call on policy makers to recognise that each border zone raises its own unique set of complex challenges that requires flexibility and special consideration by transboundary authorities in management of disasters.